Problems of legal regulation on gender-based violence in Ukraine and foreign countries (Law and Safety, 2023)
The purpose of the article is to analyse gender-based violence and to study the legal mechanisms for overcoming it in Ukraine. On the basis of scientific findings and proposals, it has been suggested that a new perspective on this issue be taken. The basic concepts of gender-based violence, its forms, and European standards that are effective in preventing and combating violence have been studied. The expediency of forming a scientifically based system of prevention, regulation and overcoming of domestic violence has been emphasised. The legislation of different countries has been analysed, the peculiarities of gender-based violence and the factors that influence its occurrence in the family have been identified. The author’s own definition for the term “gender-based violence” has been presented.Both general scientific and special methods of cognition were used in the course of the study. The logical method was used to formulate legal concepts and classify types of violence. The historical method was used to study the historical aspects and chronology of the emergence and development of gender-based violence. The use of the dialectical method has made it possible to determine the legal nature and essence of gender-based violence. The synergistic method has allowed to characterise the legal nature of gender-based violence. The axiological method was used to determine the role of the principle of gender equality in the development of Ukrainian legislation and its implementation into European legislation. The dogmatic method was used to interpret legal acts in terms of their compliance with modern European standards.Based on the analysis of regulatory acts and legal literature, the author proposes a definition of gender-based violence as an activity or behaviour aimed at maintaining the advantage of one party over another, depending on gender status. It can be physical violence, mental violence, sexual violence, economic violence, stereotypical behaviour.